An investigation to discover the various challenges faced by sugarcane farmers in Kwa-Zulu Natal - Moodley, Mishen (The IIE, 2018)
According to SASA (2009), around 2% of the South African population are dependent on the sugarcane industry for a living. This activity however faces challenges throughout the whole process. Taking this into consideration, and to understand the impact, the important question is, what are the various challenges faced by sugarcane farmers. The sample used for the study were two sugarcane farmers from Darnall, Kwa-Zulu Natal. The data was collected using a semi-structured interview schedule, as it enabled the researcher to gain an in-depth understanding of the phenomenon through exploring the experiences, views and beliefs of the participants on challenges faced by them and solutions implemented. The study found that viability and climate change are the most significant challenges facing the sugarcane farmers in Kwa-Zulu Natal. Furthermore, the study also found that the sugarcane farmers make use of their own strategies to address challenges. These strategies include outsourcing key functions, such as the use of labour for harvesting and the hire of transport companies to transport the farmer’s cane. Another strategy involves cash reserves being built up to sustain the farmer in difficult times. Recommendations were made towards the challenges faced and areas for possible future research avenues were highlighted.
Keywords: sugarcane farmers; KwaZulu-Natal; climate change; viability